Construction of a novel molecular typing and scoring system for anoikis distinguishes between different prognostic risks and treatment responsiveness in low-grade glioma - Zhang, Ganghua; Chen, Aiyan; Fang, Jianing; Wu, Anshan; Chen, Guanjun; Tai, Panpan; Chen, Haotian; Chen, Xinyu; Cao, Ke (Frontiers in Immunology, 2023)
Background The main factors responsible for low-grade glioma (LGG)s' poor prognosis and treatment effectiveness include recurrence and malignant progression. A specific type of programmed cell death, known as anoikis, which is crucial for tumor invasion and metastasis, however, has not yet been investigated in LGGs. Methods We downloaded data of 509 samples from the TCGA-LGG cohort, carried out cluster analysis for typing twice on the basis of 19 anoikis-associated genes, and the subtypes were evaluated the differences in clinicopathological and biological features. ESTAMATE and single-sample gene set enrichment analysis were employed to examine the immunological milieu of LGGs, and enrichment analysis was used to look into the underlying biological mechanisms in LGGs. Cox regression analysis and the Least Absolute Shrinkage and Selection Operator regression algorithm were used to create a prediction scoring system. The scoring system was used for classifying LGG into high- and low- anoikis riskscore (anoiS) groups. The impact of the anoiS on the prognosis, standard treatment, and immunotherapy of patients with LGG was assessed using survival analysis and drug sensitivity analysis. Cell experiments were employed for the verification of the differential expression between LGG cells and normal cells of the anoikis gene team that regard CCT5 as the core. Results Based on the expression profiles of the 19 anoikis-associated genes, all individuals with LGG were classified into four subtypes and two macrosubtypes. The different macrosubtypes had significantly different biological characteristics, and the anoirgclusterBD subtype manifested a significantly bad prognosis and a high immune level of infiltration. And subsequent secondary genotyping also showed good prognostic discrimination. We further constructed an anoikis scoring system, anoiS. LGG patients having a high anoiS had a worse prognosis in comparison to those having a low anoiS. The high anoiS group exhibited larger levels of immune infiltration and superior immunotherapy efficacy than the low anoiS group. The high anoiS group was also more susceptible to temozolomide (TMZ) than the low anoiS group, according to a drug sensitivity analysis of TMZ. Conclusion This study constructed a scoring system for predicting the prognosis of patients with LGG and their responsive to TMZ and immunotherapy.